Adolescent girl, commercial sex workers and HIV_AIDS awareness (1996)
The objective of the study is to assess the level of awareness of HIV AIDS among adolescent girls commerical sex workers in terms of the existence of HIV-AIDS in Nigeria, and the sex workers' awareness of their vulnerability to HIV-AIDS infection. The study also examined the preparedness of the commercial sex workers to quite the trade. A 20-item questionnaire HIV_AIDS awareness among commercial sex workers- was administered on the 12 adolescent commerical sex workers in the two brothels used for the study. Results indicated a high level of awreness of the existence of HIV-AIDS infection, they do not see themselves quiting the trade since they believe they already have the stigma as sex workers. The findings have implications for designing intervention strategies which can help promote behavioural change in the adolescent sex worker, and help restructure her cognitive make-up regarding her mind set about having a stigma.